Polypyrrole-Based Materials for 6G Networks: Applications and Sustainability Across Emerging Fields - Qamili, Aurela; Basholli, Fatmir; Juraev , Davron Aslonqulovich; Lami, Roland (Karshi Multidisciplinary International Scientific Journal, 2025)
Polypyrrole (PPy) is a conductive polymer that has gained significant attention for its potential in advanced materials for 6G networks. This study explores how (PPy)–based materials contribute to the development of 6G technologies, focusing on their uses, advantages, and sustainability. Due to their flexibility, conductivity, and environmental stability, these composites have a lot of potential for use in 6G networks, especially in applications like energy storage, flexible antennas, Electromagnetic Interference (EMI) shielding, and Internet of Things (IoT) sensors. The material's energy efficiency, recyclability, and tunability make it an essential part of sustainable 6G infrastructure. This study also investigates how PPy synthesis affects the environment and how it might reduce e-waste and support environmentally friendly communication networks. The potential of PPy in next-generation communication systems by emphasizing improvements in material performance and sustainability is also highlighted.